2020
DOI: 10.1186/s12866-020-01991-5
|View full text |Cite
|
Sign up to set email alerts
|

Stool microbiome, pH and short/branched chain fatty acids in infants receiving extensively hydrolyzed formula, amino acid formula, or human milk through two months of age

Abstract: Background Early infant feeding with intact or extensively hydrolyzed (EH) proteins or free amino acids (AA) may differentially affect intestinal microbiota composition and immune reactivity. This multicenter, double-blind, controlled, parallel-group, pilot study compared stool microbiota from Baseline (1–7 days of age) up to 60 days of age in healthy term infants who received mother’s own milk (assigned to human milk [HM] reference group) (n = 25) or were randomized to receive one of two infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 92 publications
1
17
0
Order By: Relevance
“…Several studies consistently showed that children fed with breast milk or formula have a clear and distinct fecal metabolome, as recently summarized by Laurens et al (Laurens et al, 2020). Targeted or non-targeted profiling of infant stool resulted in the detection of various metabolite classes including short chain fatty acids (SCFAs), amino acids, amino acid catabolites, fatty acids, human milk oligosaccharides, monosaccharides, purine degradation products or even plantbased metabolites from soy-based formula (Chow et al, 2014;Martin et al, 2014;Dotz et al, 2015;Dotz et al, 2016;Martin et al, 2016b;Bridgman et al, 2017;He et al, 2019;Brink et al, 2020;Kok et al, 2020;Li et al, 2020).…”
Section: Time Independent Feeding Effects On the Fecal Metabolomementioning
confidence: 99%
“…Several studies consistently showed that children fed with breast milk or formula have a clear and distinct fecal metabolome, as recently summarized by Laurens et al (Laurens et al, 2020). Targeted or non-targeted profiling of infant stool resulted in the detection of various metabolite classes including short chain fatty acids (SCFAs), amino acids, amino acid catabolites, fatty acids, human milk oligosaccharides, monosaccharides, purine degradation products or even plantbased metabolites from soy-based formula (Chow et al, 2014;Martin et al, 2014;Dotz et al, 2015;Dotz et al, 2016;Martin et al, 2016b;Bridgman et al, 2017;He et al, 2019;Brink et al, 2020;Kok et al, 2020;Li et al, 2020).…”
Section: Time Independent Feeding Effects On the Fecal Metabolomementioning
confidence: 99%
“…Interestingly, our observations show that gut microbiome composition differed between the infants fed HF as compared to RF-fed infants. Recent studies also indicate that hydrolyzed milk protein has a modest effect on the gut microbiome composition ( 51 , 52 ). Taken together, it is plausible that different dietary protein sources in early life may influence gut microbiotal composition and circulating lipids; however, the underlying mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Only few data are available that address a possible relationship between maternal serum and breast milk FAA (Ramírez et al 2001 ), providing results that may indicate underlying mechanisms for the emergence of these different FAA patterns in breast milk. Furthermore, hardly any study addressed the FAA composition of breast milk in lactation in relation to the infants’ intestinal microbiota (He et al 2020 ; Kok et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Provision of different sources and amounts of dietary protein was already shown to influence gut microbiota and its metabolites, e.g. when comparing breast-fed with formula-fed infants (Kok et al 2020 ). However, there is only limited data on how the different FAA in human milk relate to or even influence the composition of the infant's microbiota.…”
Section: Introductionmentioning
confidence: 99%